Understanding enterprise, entrepreneurship and small business - Bridge, Simon (Macmillan Business, 1998)
This text explores the concepts of entrepreneurship and enterprise and also ideas and trends; it is an essential guide for anyone wishing to get to grips with the complexities of small business, enterprise and entrepreneurship